Internal and External Determinants of Secondary School Teachers' Digital Literacy Effectiveness: A Systematic Literature Review - Anang Ristanto; Siswantoyo; Faqih Ma’arif (WISE Pendidikan Indonesia, 2026)
This study aims to identify and synthesize the internal and external determinants affecting the effectiveness of secondary school teachers’ digital literacy. A systematic literature review was conducted following the PRISMA 2020 guidelines, drawing on empirical studies indexed in Scopus, Web of Science, ERIC, and Google Scholar. The findings show that digital literacy effectiveness emerges from the dynamic interaction between individual capacities and institutional conditions. The most influential internal determinants are digital pedagogical competence, self-efficacy, attitudes toward technology, intrinsic motivation, and prior technological experience. Key external determinants include ICT infrastructure, school leadership, institutional support, educational policy, collaborative school culture, and continuous professional development. At the secondary level, self-efficacy and technological pedagogical content knowledge are particularly important because they shape the quality of technology integration and support students’ higher-order thinking skills. The study concludes that teacher digital literacy should be understood as a multidimensional and ecosystem-based competence. Strengthening it therefore requires coordinated policies, sustained professional development, equitable infrastructure, and supportive school cultures that promote inclusive, adaptive, and meaningful digital learning.